Biological control of the banded fruit weevil, Phlyctinus callosus (Schönherr), using entomopathogenic nematodes and fungi - Dlamini, Bonginkhosi (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhDConsEcol)--Stellenbosch University, 2018.